Design of kitting system in lean-based assembly lines - KILIÇ, HÜSEYİN SELÇUK (EMERALD GROUP PUBLISHING LIMITED, 2012)
Purpose - The purpose of this paper is to develop a mathematical model for designing the kitting system by determining the optimum values of the related design parameters. Design/methodology/approach - Main assembly feeding systems are explained with their advantages and disadvantages. Related literature is reviewed and gaps are determined. To fill the void and to be beneficial for real life lean assembly systems, the elements of the kitting system are explained in detail and a mathematical model minimizing the cost consisting of Work In Process (WIP) and number of workers for the design of a kitting system is developed. A numerical example is presented to demonstrate the applicability of the model. Findings - This paper provides a mathematical model that provides the required design parameters for a kitting system such as the tour period, the number of workers and the quantities of the kits by minimizing WIP and labor costs. Originality/value - The paper provides a mathematical model for the design of a kitting system.
Keywords: Assembly lines; Lean production; Parts; Assembly feeding; Kitting; Mixed integer LP model; PERFORMANCE; STOCKING; KITS